A preliminary study in Er:YAG laser debonding of lithium disilicate crowns: Laser power setting vs crown thickness - GÖZNELİ, RİFAT (My University, 2023)
Background: Er:YAG laser is widely used in debonding of all-ceramic veneers nowadays. However, the data about laser parameters in all-ceramic crown removal is limited. The aim of this preliminary study was to determine the most appropriate laser parameters at safe heat transmission values for lithium disilicate crowns in different thicknesses. Methods: Twenty-seven intact premolars were prepared to fabricate lithium disilicate CAD/CAM full-coverage crowns in three different thicknesses: 1, 1.5 mm, and mixed thickness (n=9). Each thickness group was divided into 3 subgroups and subjected to Er:YAG laser at different wattages (5, 5.6 and 5.9 W) to determine the appropriate wattage for each thickness. The removal time and temperature rise values were recorded. The Kruskal-Wallis test was performed to evaluate any significant differences in removal time, Mann-Whitney U test with Bonferroni correction for multiple comparisons, and the Pearson chi-square test for temperature rise over the critical value (p<0.05). Results: Laser irradiation at 5 W was safe and efficient for 1 mm thickness, while not efficient for others. Laser application at 5.9 W was efficient for all thicknesses, but, not safe for 1 mm thickness. The statistically significant difference in removal time was only between 5 W and 5.9 W groups (p=0.035). Pearson’s chi-square test revealed that the temperature rise after 5.9 W laser application was significantly different from 5 W in 1 mm thickness group (p=0.043). Conclusion: Er:YAG laser lithium disilicate crown removal is an effective and safe method using laser settings appropriate for crown thickness.
Keywords: Crown removal; Debonding; Er:YAG laser; Heat transmission; Lithium disilicate